Mirizzi's syndrome: A scoring system for preoperative diagnosis - Rachana D Tataria; Hrishikesh P Salgaonkar; Gaurav Maheshwari; Premashish J Halder (The Saudi Journal of Gastroenterology, 2018)
Background/Aim: Mirizzi's syndrome (MS) is an unusual complication of gallstone disease and occurs in approximately 1% of patients with cholelithiasis. Majority of cases are not identified preoperatively, despite the availability of modern imaging techniques. A preoperative diagnosis can forewarn the operating surgeon and avoid bile duct injuries in cases of complicated cholecystitis. A preoperative scoring system helpful and hence, we aim to devise a scoring system based on clinical, biochemical, and imaging features to predict the diagnosis of MS in cases of complicated cholecystitis. Patients and Methods: From January 2000 to July 2013, 1,539 patients with cholelithiasis underwent cholecystectomy. Of these, 96 patients had complicated cholecystitis. Records of these patients were analyzed retrospectively. In these, 32 patients were found to be having MS that formed the study group. A scoring system was devised based on clinical, biochemical, and imaging parameters to predict the diagnosis of MS. Every positive parameter was given 1 point and patients rated on a scale of 0–10. Results: Score of 3 or more was found to have a 90% sensitivity of predicting MS among complicated cholecystitis. Similarly, a score of 6 or more had an 80% sensitivity of predicting Mirizzi's types II, III, and IV indicating fistulization. Jaundice, leucocytosis, associated choledocholithiasis/hepatolithiasis, intrahepatic biliary radical dilatation, meniscus sign and mass at confluence were found to be significant parameters. Conclusion: We propose a simple scoring system based on clinical, biochemical, and imaging parameters that can be useful for predicting MS in patients with complicated cholecystitis.